A study on recent tendency of anti-tumor herbal acupuncture - Yoo Hwa-Seung; Lee Yong-Yeon; Cho Jung-Hyo; Lee Yeon-Weol; Son Chang-Gue; Cho Chong-Kwan; Hwang Kyu-Jeong (Korean Pharmacopuncture Institute, 2001)
Objectives: The purpose of this study is to develop and activate anti-tumor herbal acupuncture for cancer patients in South Korea. Methods: We investigated some literatures on anti-tumor herbal acupuncture which is used in South Korea and China, and made diagrams. Results: The results are summarized as follows. Anti-tumor herbal acupuncture is one of the traditional oriental medical method which is effective for cancer patients. In domestic studies, most of herb materials are belong to action of cooling&detoxification(25.0%) and strengthening body resistance(46.4%) which are proved to have effects of anti-tumor, immune activation and preventing tumor. In China, point injection therapy are used for improving symptoms of cancer patients and healing tumor. Also herbal intravenous injection is used for combination of chinese traditional and western cancer therapy and treating cancer patients variously. Conclusions: From the above results, it is expected that anti-tumor herbal acupuncture is useful to improve clinical symptoms and quality of life(QOL) of cancer patients. Also we must develop new progressive methods of point injection and herbal intravenous injection for treating cancer patients, and advance clinical studies and trials.